Knowledge and attitudes about using the internet issues sexual and reproductive health - De La Mata Huapaya, Rosario (2017)
The study was conducted to evaluate the level of  evaluating the level of knowledge and attitude of the students on the use of the Internet in subjects of sexual health and reproductive CEPREVAL - Huánuco, 2011. For the study one considered the types of descriptive investigation - analytical - Prospective - Longitudinal, with a corelational descriptive design; one worked with a representative sample of 309 students divided in five areas: for the data collection a Questionnaire to measure the knowledge level and a scale of Likert were used like instrument to evaluate the attitude. For such effect, they reached the following conclusions: A percentage of 52,8% of students presented/displayed deficient knowledge on the use of the Internet in the subjects of sexual and reproductive health unlike the 56,3% of students who presented/displayed positive attitude to these subjects. As far as the contrast and test of hypothesis the result was: p: 0.05 = 5,99 75,4 Hl.